Political change and electoral coalitions in Western democracies - Hall, Peter A. 1950-; Evans, Georgina 1977-; Kim, Sung In (Cambridge elements, 2023)
This text documents long-term changes in the political attitudes of occupational groups, shifts in the salience of economic and cultural issues, and the movement of political parties in the electoral space from 1990 to 2018 in eight Western democracies